Comparative perspective on antemortem tooth loss in Neandertals. Issue 92 (March 2016) - Gilmore, Cassandra C.; Weaver, Timothy D.
Abstract: Neandertal specimens with severe antemortem (before death) tooth loss (AMTL) are sometimes interpreted as evidence for human-like behaviors in Neandertals, such as conspecific care or cooking, although it is uncertain whether AMTL frequencies in Neandertals are similar to those in modern humans and exceed those in non-human primates. This study characterizes AMTL (all tooth types) in Neandertals relative to recent human hunter-gatherers and several non-human primate taxa using binomial-normal regression models fit in a Bayesian framework to a sample of 25 Neandertals, 310 recent human hunter-gatherers, 61 chimpanzees, 38 orangutans, and 75 baboons. The probability that a tooth is lost antemortem is modeled to depend on tooth class, taxon, and estimated age at death. Neandertals have odds of AMTL above orangutans and baboons, similar to or somewhat lower than chimpanzees, and below recent humans, if we assume a human-like rate of senescence; or intermediate between chimpanzees and recent humans, if we assume a faster rate of senescence. These findings suggest that Neandertals can only be considered to have frequencies of AMTL above non-human primates if they had more rapid life histories than modern humans. Either Neandertals are not human-like in their life history or their frequency of AMTL. These interpretations are complicated, however, by the substantial inter-population variation in AMTL among recent humans, with some populations having odds of AMTL as low as in non-human primates. These results, together with theoretical considerations, suggest that only high frequencies of AMTL are diagnostic of behavior. Consequently, the behavioral implications of low frequencies of AMTL, such as those found in Neandertals, are ambiguous. Low frequencies in Neandertals could be because they had a low risk of AMTL rather than because they had high mortality from AMTL relative to an average modern human of similar age.